Perovskite quantum dot glass with adjustable luminous intensity and preparation method and application thereof
Patent Information
- Application Number
- CN202611147638.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]然而,随着技术向着动态化和智能化方向不断演进,仅仅获得一种发光性能稳定的静态材料已不能满足未来高级应用的需求
本发明通过采用包含ZnO、B2O3和SiO2的多组分玻璃体系,并结合高温熔融与精确控制的梯度热处理工艺,在熔融过程中形成高度均匀的玻璃网络结构,AlF3的引入有效调节了玻璃的结构单元,促进了玻璃基质的致密化与稳定化。在后续的热处理阶段,通过温度和时间的合理控制,实现了CsPbBr3量子点在玻璃基体中的有序析晶和尺寸精确限制。使量子点尺寸分布更加均一,减少了晶体缺陷和非辐射复合中心的形成,因而所得材料展现出明显的窄带发射特性,光谱半峰宽明显缩小,光色纯度得到显著提升。所形成的玻璃基质为量子点提供了良好的封装环境。其三维网状结构有效阻隔了环境中的水分和氧气对量子点的侵蚀,显著提升了材料的环境稳定性,使得量子点在长期高湿高温环境下仍能保持良好发光性能,体现出优异的耐久性和安全性。
Smart Images

Figure CN122916433A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of luminescent materials technology, specifically to a perovskite quantum dot glass with adjustable luminescence intensity, its preparation method, and its applications. Background Technology
[0002] Luminescent materials are at the heart of modern optoelectronic technology, widely used in key areas such as everyday lighting, high-definition displays, and information science. Among them, all-inorganic halide perovskite quantum dots (PQDs) have attracted much attention due to their superior optical properties, such as near-perfect photoluminescence quantum yield, extremely narrow full width at half maximum (FWHM), and broad spectral tunability covering the entire visible light region, and are considered a highly promising next-generation luminescent material. However, the practical application of PQDs faces a severe challenge—their inherent ionic crystal structure is extremely sensitive to environmental factors such as water, oxygen, heat, and light, resulting in severely insufficient stability and easy decay and quenching of luminescent performance in real-world environments. This inherent defect greatly limits their commercial application.
[0003] To overcome this stability bottleneck, embedding PQDs into an inert inorganic glass matrix via in-situ crystallization is a recognized and highly effective strategy. The dense three-dimensional glass network structure provides both physical and chemical protection for the internal PQDs, effectively isolating them from external environmental corrosion and significantly improving their chemical, thermal, and optical stability. Currently, researchers have successfully prepared highly stable PQDs composite glasses in various glass systems, including borosilicate, phosphate, and tellurate, laying a solid foundation for their practical applications.
[0004] However, as technology continues to evolve towards dynamism and intelligence, simply obtaining a static material with stable luminescence properties is no longer sufficient to meet the demands of future advanced applications. For example, in cutting-edge fields such as rewritable optical information storage, intelligent anti-counterfeiting, dynamic sensing, and interactive displays, there is an urgent need to actively and in real-time control the luminescence intensity of materials. Therefore, after solving the stability problem, exploring a technical means to non-destructively, quickly, and conveniently control the luminescence intensity of perovskite quantum dot glass is key to advancing this material from "static luminescence" to "dynamic functionalization" applications. Summary of the Invention
[0005] The purpose of this invention is to provide a perovskite quantum dot glass with adjustable luminescence intensity, its preparation method and application. The quantum dot glass contains Nd ions, and its luminescence intensity is reduced to less than 5% after irradiation with a 360nm laser. It can be restored to its original luminescence intensity after heat treatment.
[0006] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution: A perovskite quantum dot glass with adjustable luminescence intensity, the quantum dot glass being composed of an inorganic glass matrix containing Nd ions and perovskite quantum dots precipitated in situ in the inorganic glass matrix; after being irradiated with a 360nm laser, the luminescence intensity of the quantum dot glass decreases to less than 5% of the intensity before irradiation; and after heat treatment, the luminescence intensity recovers to the level before irradiation.
[0007] Furthermore, the inorganic glass matrix comprises at least SiO2, B2O3, ZnO and AlF3.
[0008] Furthermore, the content of Nd ions in the quantum dot glass, calculated as introduced Nd2O3, accounts for 0.1% to 1% of the total mass of the quantum dot glass.
[0009] Furthermore, the mass percentage of the Nd2O3 is 0.5% to 0.8%.
[0010] Furthermore, the quantum dot glass, when excited by 365nm ultraviolet light, produces narrow-band emission with a full width at half maximum (FWHM) of ≤20nm; wherein the perovskite quantum dot is CsPbBr3, and its emission peak is located at 515±5nm.
[0011] On the other hand, the present invention proposes a method for preparing the above-mentioned perovskite quantum dot glass with tunable luminescence intensity, comprising the following steps: S1: Weigh the raw materials by mass percentage: SiO2: 15%~20%, B2O3: 25%~30%, ZnO: 15%~20%, AlF3: 5%~10%, K2CO3: 5%~10%, Cs2CO3: 5%~8%, PbX2: 5%~8%, NaX: 10%~15%, and Nd2O3 as the source of Nd ions: 0.1%~1%, wherein X is at least one of Cl, Br or I; mix and grind the raw materials. S2: Sinter the ground raw material at 1350℃ for 10-15 minutes in air atmosphere to obtain glass melt; S3: Transfer the glass melt to a brass mold preheated to 400°C and hold it for 15 minutes to form the precursor glass; S4: The precursor glass is kept at 480°C for 3 hours to precipitate perovskite quantum dots in situ, and then cooled to room temperature in the furnace to obtain the annealed glass. S5: Grind and polish the annealed glass to obtain the perovskite quantum dot glass.
[0012] Furthermore, in step S1, the X in PbX2 and NaX is Br, so that the prepared perovskite quantum dots are CsPbBr3; the mass percentage of Nd2O3 is 0.5%~0.8%.
[0013] On the other hand, the present invention proposes an optical information storage and dynamic display device comprising the aforementioned perovskite quantum dot glass.
[0014] On the other hand, the present invention proposes the application of the above-mentioned perovskite quantum dot glass in the preparation of anti-counterfeiting devices or optical switching devices.
[0015] The beneficial effects of this invention are: This invention employs a multi-component glass system containing ZnO, B2O3, and SiO2, combined with a high-temperature melting and precisely controlled gradient heat treatment process. During melting, a highly uniform glass network structure is formed. The introduction of AlF3 effectively regulates the structural units of the glass, promoting the densification and stabilization of the glass matrix. In the subsequent heat treatment stage, through rational control of temperature and time, ordered crystallization and precise size confinement of CsPbBr3 quantum dots within the glass matrix are achieved. This results in a more uniform quantum dot size distribution, reduces the formation of crystal defects and non-radiative recombination centers, and thus the obtained material exhibits a significant narrow-band emission characteristic, a markedly reduced spectral half-width, and a significantly improved color purity. The formed glass matrix provides an excellent encapsulation environment for the quantum dots. Its three-dimensional network structure effectively blocks the erosion of quantum dots by moisture and oxygen in the environment, significantly improving the environmental stability of the material. This allows the quantum dots to maintain good luminescence performance even under long-term high humidity and high temperature environments, demonstrating excellent durability and safety.
[0016] This invention employs an all-inorganic melting method to prepare glass quantum dot materials, avoiding the use of organic surface ligands and related organic solvents commonly used in traditional hot-injection methods, thus achieving a green and environmentally friendly preparation process. The rational optimization of the melting temperature and the application of fluxing components ensure the stable existence of high ZnO content in the glass system, guaranteeing the uniformity and density of the glass matrix. This process not only simplifies the production steps but also eliminates environmental pollution and safety hazards caused by the volatilization of organic matter, improving the sustainability and industrialization potential of production.
[0017] Simultaneously, this invention achieves modulation of the luminescence intensity of PQDs through 360nm laser irradiation. Unlike modulation methods such as heat treatment or alteration of synthesis ratios, which may damage the glass matrix or cause irreversible structural changes, optical field modulation utilizes the interaction between photon energy and quantum dot excitons to achieve instantaneous adjustment of luminescence intensity without altering the material's physicochemical structure. This non-contact, non-destructive, and easily manipulated modulation method not only protects the high stability of the glass matrix but also achieves rapid response, meeting the real-time processing requirements of fast-moving dynamic information. Furthermore, using optical field modulation of the luminescence intensity of PQDs glass facilitates the "write-erase-rewrite" cycle of information. Due to the excellent chemical inertness and thermal stability of the glass matrix, this optically modulated information storage exhibits extremely high long-term preservation and anti-interference capabilities, far exceeding those of traditional organic materials.
[0018] Achieving light-field-controlled perovskite quantum dot glass not only solves the problem of poor stability in traditional materials, but also greatly expands the functional dimensions of materials by introducing a dynamic, non-destructive, and rapid light response mechanism, making it a key bridge connecting basic materials science and future intelligent optoelectronic applications.
[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The XRD patterns of the perovskite quantum dot glass samples in Examples 1-4 are shown. Figure 2 The images show the physical photographs of the CsPbBr3 perovskite quantum dot glass in Example 2 after irradiation with a 360nm laser and its luminescence under a 365nm ultraviolet lamp. Figure 3 The transmission spectra of the CsPbBr3 perovskite quantum dot glass in Example 2 before and after 360nm laser irradiation are shown. Figure 4 The emission spectra of the CsPbBr3 perovskite quantum dot glass in Example 2 before and after 360nm laser irradiation are shown. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1
[0024] In this embodiment, a method for preparing perovskite quantum dot glass with tunable luminescence properties is provided, comprising the following steps: Weigh the following raw materials: SiO2: 20%, B2O3: 27%, AlF3: 7%, K2CO3: 5%, ZnO: 17%, Cs2CO3: 5%, PbBr2: 5%, NaBr: 13.9%, Nd2O3: 0.1% All percentages mentioned above are by mass, and the total mass is 10 g. Place the above raw materials in an agate mortar and grind them until evenly mixed.
[0025] The ground mixture was transferred to a high-temperature box furnace and sintered at 1350 °C for 15 min in an air atmosphere to obtain glass melt.
[0026] The resulting glass melt was transferred to a brass mold preheated to 400 °C and held for 15 min to form the precursor glass.
[0027] After the precursor glass is cooled to room temperature (20-30°C), it is transferred to a small German furnace and held at 480°C for 3 hours. Then, it is cooled to room temperature with the furnace to obtain the annealed glass.
[0028] The annealed glass is ground and polished on a polishing machine to obtain shaped perovskite quantum dot glass.
[0029] The X-ray diffraction pattern of the perovskite quantum dot glass prepared in this embodiment is shown in the appendix to this specification. Figure 1 As shown in the figure, the spectrum reveals distinct diffraction peaks in the glass matrix that match those of the standard card, confirming the successful precipitation of nanocrystalline quantum dots.
[0030] Example 2
[0031] In this embodiment, a method for preparing perovskite quantum dot glass with tunable luminescence properties is provided, comprising the following steps: Weigh the following raw materials: SiO2: 20%, B2O3: 27%, AlF3: 7%, K2CO3: 5%, ZnO: 17%, Cs2CO3: 5%, PbBr2: 5%, NaBr: 13.5%, Nd2O3: 0.5% All percentages mentioned above are by mass, and the total mass is 10 g. Place the above raw materials in an agate mortar and grind them until evenly mixed.
[0032] The ground mixture was transferred to a high-temperature box furnace and sintered at 1350 °C for 15 min in an air atmosphere to obtain glass melt.
[0033] The resulting glass melt was transferred to a brass mold preheated to 400 °C and held for 15 min to form the precursor glass.
[0034] After the precursor glass was cooled to room temperature, it was transferred to a small German furnace and held at 480 °C for 3 hours. After that, it was cooled to room temperature with the furnace to obtain the annealed glass.
[0035] The annealed glass is ground and polished on a polishing machine to obtain shaped perovskite quantum dot glass.
[0036] In this embodiment, the properties of the prepared CsPbBr3 perovskite quantum dot glass were characterized. Photographs of the glass after 360 nm laser irradiation and its emission under a 365 nm ultraviolet lamp are attached to this specification. Figure 2 As shown, this glass has high transmittance and is yellowish-green in color; after being irradiated with a 360 nm laser, its luminescence is significantly reduced.
[0037] The transmission spectra of the glass before and after 360 nm laser irradiation are shown in the appendix to this specification. Figure 3 As shown, after laser irradiation, its transmission spectrum did not show significant changes, indicating that the sample has the potential for encryption and anti-counterfeiting applications.
[0038] The emission spectra of the glass before and after 360 nm laser irradiation are shown in the appendix to this specification. Figure 4 As shown, after irradiation with a 360 nm laser, the luminescence intensity of the sample decreased to less than 5% of its pre-irradiation intensity. Subsequently, the laser-irradiated sample underwent heat treatment, and its luminescence intensity recovered to the pre-irradiation level. This reversible process confirms the dynamic light modulation function achieved by the technical solution of this invention.
[0039] Example 3
[0040] In this embodiment, a method for preparing perovskite quantum dot glass with tunable luminescence properties is provided, comprising the following steps: Weigh the following raw materials: SiO2: 20%, B2O3: 27%, AlF3: 7%, K2CO3: 5%, ZnO: 15%, Cs2CO3: 5%, PbBr2: 7%, NaBr: 13.5%, Nd2O3: 0.5% All percentages mentioned above are by mass, and the total mass is 10 g. Place the above raw materials in an agate mortar and grind them until evenly mixed.
[0041] The ground mixture was transferred to a high-temperature box furnace and sintered at 1350 °C for 15 min in an air atmosphere to obtain glass melt.
[0042] The resulting glass melt was transferred to a brass mold preheated to 400 °C and held for 15 min to form the precursor glass.
[0043] After the precursor glass was cooled to room temperature, it was transferred to a small German furnace and held at 480 °C for 3 hours. After that, it was cooled to room temperature with the furnace to obtain the annealed glass.
[0044] The annealed glass is ground and polished on a polishing machine to obtain shaped perovskite quantum dot glass.
[0045] In this embodiment, by adjusting the ratio of ZnO to PbBr2, the glass system of the present invention demonstrates good tolerance to compositional changes. The resulting glass also exhibits narrow-band light emission characteristics and reversible light control performance.
[0046] Example 4
[0047] In this embodiment, a method for preparing perovskite quantum dot glass with tunable luminescence properties is provided, comprising the following steps: Weigh the following raw materials: SiO2: 20%, B2O3: 27%, AlF3: 7%, K2CO3: 5%, ZnO: 17%, Cs2CO3: 5%, PbBr2: 5%, NaBr: 13.2%, Nd2O3: 0.8% All percentages mentioned above are by mass, and the total mass is 10 g. Place the above raw materials in an agate mortar and grind them until evenly mixed.
[0048] The ground mixture was transferred to a high-temperature box furnace and sintered at 1350 °C for 15 min in an air atmosphere to obtain glass melt.
[0049] The resulting glass melt was transferred to a brass mold preheated to 400 °C and held for 15 min to form the precursor glass.
[0050] After the precursor glass was cooled to room temperature, it was transferred to a small German furnace and held at 480 °C for 3 hours. After that, it was cooled to room temperature with the furnace to obtain the annealed glass.
[0051] The annealed glass is ground and polished on a polishing machine to obtain shaped perovskite quantum dot glass.
[0052] It should be understood that the above embodiments 1 to 4 only illustrate the present invention using PbBr2 and NaBr as examples, but the scope of protection of the present invention is not limited thereto. In some embodiments, halogen X is selected from at least one of Cl, Br, or I. By adjusting the halogen composition, the emission wavelength of perovskite quantum dots can be adjusted to cover the entire visible light region.
[0053] In some embodiments, the amount of Nd2O3 introduced is 0.1% to 1% by mass. By adjusting the content of Nd2O3, the sensitivity and efficiency of photomodulation can be adjusted.
[0054] In some embodiments, the perovskite quantum dot glass prepared according to the present invention produces narrow-band emission with a full width at half maximum (FWHM) of less than or equal to 20 nm under 365 nm ultraviolet light excitation. When the perovskite quantum dots contained are CsPbBr3, their emission peak is located at 515 nm ± 5 nm.
[0055] It should be understood that the perovskite quantum dot glass prepared by this invention has application potential in the fields of display devices, solid-state lighting devices, optical information storage, dynamic displays, anti-counterfeiting devices, and optical switching devices. The luminous intensity can be attenuated by writing using 360 nm laser irradiation, and then the information can be erased and restored through heat treatment, thus forming a complete write-erase-rewrite cycle.
[0056] In summary, this invention proposes a perovskite quantum dot glass with tunable luminescence intensity, its preparation method, and its applications. The quantum dot glass is composed of an inorganic glass matrix doped with Nd ions and perovskite quantum dots precipitated in situ within it. During preparation, SiO2, B2O3, ZnO, AlF3, K2CO3, Cs2CO3, PbX2, NaX, and Nd2O3 are weighed according to a specific ratio, mixed and ground, and then melted at 1350℃. Controllable crystallization of the quantum dots is achieved through gradient heat treatment and annealing. The resulting glass exhibits narrow-band luminescence with a full width at half maximum (FWHM) ≤ 20 nm under 365 nm ultraviolet light excitation. Irradiation with a 360 nm laser can attenuate the luminescence intensity to less than 5% of its pre-irradiation intensity, which can be restored to the original level after heat treatment, achieving non-destructive and reversible control of the luminescence intensity. This invention has broad application potential in fields such as optical information storage, dynamic display, and anti-counterfeiting devices.
[0057] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A perovskite quantum dot glass with tunable luminescence intensity, characterized in that, The quantum dot glass is composed of an inorganic glass matrix containing Nd ions and perovskite quantum dots precipitated in situ in the inorganic glass matrix; after being irradiated with a 360nm laser, the luminescence intensity of the quantum dot glass is reduced to less than 5% of the intensity before irradiation; and after heat treatment, its luminescence intensity is restored to the level before irradiation.
2. The perovskite quantum dot glass as described in claim 1, characterized in that, The inorganic glass matrix comprises at least SiO2, B2O3, ZnO, and AlF3.
3. The perovskite quantum dot glass as described in claim 1 or 2, characterized in that, The content of Nd ions in the quantum dot glass, based on the introduced Nd2O3, is 0.1% to 1% of the total mass of the quantum dot glass.
4. The perovskite quantum dot glass as described in claim 3, characterized in that, The mass percentage of Nd2O3 is 0.5% to 0.8%.
5. The perovskite quantum dot glass as described in claim 1, characterized in that, The quantum dot glass produces narrow-band emission with a half-width of ≤20nm when excited by 365nm ultraviolet light; wherein the perovskite quantum dot is CsPbBr3, and its emission peak is located at 515±5nm.
6. A method for preparing perovskite quantum dot glass with tunable luminescence intensity as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Weigh the raw materials by mass percentage: SiO2: 15%~20%, B2O3: 25%~30%, ZnO: 15%~20%, AlF3: 5%~10%, K2CO3: 5%~10%, Cs2CO3: 5%~8%, PbX2: 5%~8%, NaX: 10%~15%, and Nd2O3 as the source of Nd ions: 0.1%~1%, wherein X is at least one of Cl, Br or I; mix and grind the raw materials. S2: Sinter the ground raw material at 1350℃ for 10-15 minutes in air atmosphere to obtain glass melt; S3: Transfer the glass melt to a brass mold preheated to 400°C and hold it for 15 minutes to form the precursor glass; S4: Cool the precursor glass to 20-30°C, hold it at 480°C for 3 hours to precipitate perovskite quantum dots in situ, and then cool it to room temperature in the furnace to obtain the annealed glass. S5: Grind and polish the annealed glass to obtain the perovskite quantum dot glass.
7. The preparation method according to claim 6, characterized in that, In step S1, the X in PbX2 and NaX is Br, so that the prepared perovskite quantum dots are CsPbBr3; the mass percentage of Nd2O3 is 0.5%~0.8%.
8. An optical information storage and dynamic display device, characterized in that, It comprises a perovskite quantum dot glass as described in any one of claims 1 to 5.
9. The use of the perovskite quantum dot glass as described in any one of claims 1 to 5 in the fabrication of anti-counterfeiting devices or optical switching devices.